Trauma of bone and soft tissues in South American mummies—New cases provide further insight into violence and lethal outcome - Begerock, Anna-Maria; Loynes, Robert; Peschel, Oliver K.; Verano, John; Bianucci, Raffaella; Martinez Armijo, Isabel; González, Mercedes; Nerlich, Andreas G. (Frontiers in Medicine, 2022)
There exist numerous reports on violence in South American populations which shed a particular light on life and living conditions in those historic communities. Most studies have been performed on collections of isolated skulls. Whole-body investigations especially on well-preserved mummified human remains are rare. In our present study we investigated three South American mummies dating between 900 – 1300 CE by an interdisciplinary approach with the particular intention to identify trauma sequels and to evaluate their paleoforensic potential. In the first mummy, we detected a perimortem attack against the right face with fresh fractures of the zygoma. The additional detection of a small wound at the dorsal thorax and a wound track reaching the thoracic aorta strongly suggest a targeted stabbing attack which – in this constellation – led to rapid death by massive bleeding. In the second case an old healed fracture of the right skull indicates an antemortem injury that was followed by a perimortem de-novo blow against the left skull with a skull defect and fresh fractures of the frontal bone. In addition, a massive torsion trauma of the cervical spine caused immediate death by disruption of the cervical spinal cord. In the third individual multiple possible injuries were detected which, however, proved to be all of post-mortem origin and not-related to death or previous trauma. Our study provides clear evidence that a careful interdisciplinary investigation of well preserved human remains may detect much more frequent traces of intentional trauma than previously thought. Particularly, trauma against the body may not be identified in studies on skulls alone, and trauma residues of internal organs/ soft tissues will only be seen in mummies. We therefore postulate an even higher (lethal) trauma rate in various South American populations than previously estimated.